The imbalance of Treg/Th17 cells induced by perinatal bisphenol A exposure is associated with activation of the PI3K/Akt/mTOR signaling pathway in male offspring mice. (March 2020) - Gao, Liang; Dong, Youdan; Lin, Ren; Meng, Yuan; Wu, Fengjuan; Jia, Lihong
Abstract: Bisphenol A (BPA) can inhibit the differentiation and function of regulatory T cells (Treg), and affect the balance of helper T cell (Th) 1/Th2, therefore, the immunotoxicity of BPA has attracted widespread attention in recent years, but its mechanism is not clear. The main aim of this study was to explore the regulatory mechanism of the PI3K/Akt/mTOR signaling pathway in the context of perinatal exposure to BPA-induced Treg/Th17 imbalance in male offspring mice through a combination of in vivo and in vitro methods. Our results showed that perinatal exposure to BPA could increase the number of Th17 cells while decreasing Treg cell numbers, which was consistent with the expression levels of up-regulation of RORγt protein and a down-regulation FOXP3 protein in the splenocytes of the male offspring mice. BPA could activate the PI3K/Akt/mTOR signaling pathway and increase the inflammatory response, as evidenced by higher serum IL-17 and TNF-α levels by inducing the activation of the AhR and TLR4/NF-κB signaling pathways. Moreover, our results also supported the hypothesis whereby the Treg/Th17 imbalance, induced by perinatal exposure to BPA, was associated with the activation of PI3K/Akt/mTOR signaling in vitro -cultured peripheral blood mononuclear cells by using rapamycin as an inhibitor of mTOR. Highlights: Perinatal BPA exposure resulted in the imbalance of Treg/Th17 in male offspring mice by activating PI3K/Akt/mTOR pathway. Perinatal BPA exposure increased the inflammatory response by activating the AhR and TLR4/NF-κB pathways. The key windows of BPA immunotoxicity were pregnancy and lactation.